Dispersible hydrogel force sensors reveal patterns of solid mechanical stress in multicellular spheroid cultures - Wontae Lee (Nature Portfolio, 2019)
Understanding how forces orchestrate tissue formation requires technologies to map internal tissue stress at cellular length scales. Here, authors develop ultrasoft sensors that visibly deform under cell-generated stress to capture patterns of internal stress development during multicellular spheroid formation.